Evaluating emotional response to products: The case of dishwashers - BAĞLI, HATİCE HÜMANUR (My University, 2024)
As the online shopping market proliferates, designers are pushed to start designing for pre-use user experience, focusing on how the user experiences the product during online shopping, namely before actual use. The goal of this study is to provide input to design professionals, helping them to design for pre-use user experience, in other words, design for products sold in the online shopping market. This study sheds light on pre-use user experience by proposing a questionnaire-based method investigating the \"affect\" dimension of UX. Throughout the study, following two pilot studies and an optimization process, 7 dimensions, which can be rated on a 5-point Likert scale, are generated to assess the emotional response to the dishwasher samples. While proposing a self-reported, practical, cost-efficient, quantifiable method to evaluate the \"affect\" dimension in UX, this study also posits a framework that can be used to adapt the method to other product genres.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Sanat; İç Mimarlık; İnşaat Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Art; Interior Architecture; Civil Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Mühendislik; Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; SANAT; MİMARİ; KENTSEL ÇALIŞMALAR; MÜHENDİSLİK, İNŞAAT; Engineering, Computing & Technology (ENG); Arts & Humanities (AHCI); Social Sciences (SOC); ENGINEERING; ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; ART; ARCHITECTURE; URBAN STUDIES; ENGINEERING, CIVIL; İnşaat ve Yapı Mühendisliği; Fizik Bilimleri; Mimari; Görsel Sanatlar ve Gösteri Sanatları; Sosyal Bilimler ve Beşeri Bilimler; Kentsel çalışmalar; Civil and Structural Engineering; Physical Sciences; Architecture; Visual Arts and Performing Arts; Social Sciences & Humanities; Urban Studies; Affect; Design research; Emotional response; Online shopping; User experience